A Structural Equation Model of Factors Influencing Employee Retention in Accounting Audit’s Firms as Approved by the Securities and Exchange Commission (SEC), Thailand . - Rungwareepaisarn, Pornthirak (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aims to study the factors influencing employee’s retention and also to investigate the relationship of empirical data and a causal model of the influences of transformational leadership, work motivation, perceived organizational support, job satisfaction and organizational commitment of employees in the accounting audit’s firms as approved by The Securities and Exchange Commission (SEC), Thailand. This research is the mixed methods research, combining of both quantitative and qualitative researches. The qualitative research was conducted by 5 in-depth interviews with executives. The quantitative research is empirical research, in which the questionnaire was used as a tool to collect data from the sample i.e. 400 employees of the auditing’s firms as approved by SEC. The statistical scales used in the research were descriptive statistics, frequency, percentage, standard deviation, hypothesis testing and Structural Equation Modeling (SEM) models through Confirmatory Factor Analysis (CFA) and Path Analysis by using the software package and the results are used in the discussion. The research found that 1) The overall fit of measurement model of employee’s retention, also showed that adjusted goodness of fit as indices. 2) The employee’s retention is influenced by the direct effect from transformational leadership (g=0.54) and job satisfaction (ß=0.52) respectively. It is influenced by the indirect effect from perceived organizational support (g=0.36) and work motivation (g=0.16) respectively. Also, it is influenced by the total effect from transformational leadership (g=0.61), job satisfaction (ß=0.55), work motivation (g=0.33), organizational commitment (ß=0.07), and perceived organizational support (g=0.03) respectively. 3) The results of the hypothesis testing are largely based on the hypothesis assumptions, except for transformational leadership has found negative influence on organizational commitment and also perceived organizational support has found negative influence on the retention of employees in the organization. Therefore, the executives of the accounting’s audit firms should focus on promoting and developing the transformational leadership skills for their managers or supervisors in the organization to create more job satisfaction for employees. This will reduce the probability of leaving a job and increase the long-term viability of the organization. Article history : Received 11 December 2018 Revised 22 December 2018 Accepted 24 December 2018 SIMILARITY INDEX = 1.21